2013
DOI: 10.1103/physrevb.87.035118
|View full text |Cite
|
Sign up to set email alerts
|

Determining binding energies of valence-band electrons in insulators and semiconductors via lanthanide spectroscopy

Abstract: Models and methods to determine the absolute binding energy of 4f -shell electrons in lanthanide dopants will be combined with data on the energy of electron transfer from the valence band to a lanthanide dopant. This work will show that it provides a powerful tool to determine the absolute binding energy of valence band electrons throughout the entire family of insulator and semiconductor compounds. The tool will be applied to 28 fluoride, oxide, and nitride compounds providing the work function and electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
104
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 96 publications
11
104
0
Order By: Relevance
“…7. The energy difference E VC between the top of the valence band at E V and the bottom of the conduction band at E C is taken 8% larger than the exciton creation energy E ex ¼ 8.45 eV in order to account for the estimated exciton binding energy [18]. E CT defines the energy difference between E V and the ground state energy E 4f (7,2þ,A) of Eu 2 þ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7. The energy difference E VC between the top of the valence band at E V and the bottom of the conduction band at E C is taken 8% larger than the exciton creation energy E ex ¼ 8.45 eV in order to account for the estimated exciton binding energy [18]. E CT defines the energy difference between E V and the ground state energy E 4f (7,2þ,A) of Eu 2 þ .…”
Section: Discussionmentioning
confidence: 99%
“…Such scheme provides a new method for the visualization of the location of the relevant lanthanide states with respect to each other and to the bands of the host compound. The first VRBE schemes were constructed for fluorides, aluminates, nitride compounds [18] and also already presented for some oxide materials [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of TiO 2 , bondlengths around a lanthanide on those sites will be smaller too resulting in smaller centroid energy and U (6, A). We therefore estimate for TiO 2 and ZnO U (6, A) ≈ 6.7 eV and for SnO 2 with the larger value for χ U (6, A) ≈ 6.8 eV. Figure 1 shows the VRBE for all lanthanide states when a value of 6.7 eV is used for U (6, A).…”
Section: Methodsmentioning
confidence: 99%
“…and full consistency with available experimental data from different fields of science was demonstrated. [2][3][4] It was found that in inorganic compounds based on rare earth cations, like YPO 4 and LaBO 3 , and/or alkaline and/or alkaline earth cations like CaF 2 and CaGa 2 S 4 , the binding energy at the bottom of the conduction band E C is typically near −2 eV. Sc-based compounds like ScBO 3 and ScPO 4 tend to show lower values for E C which was attributed to a large binding energy of electrons in the 3d-shell of Sc 3+ /Sc 2+ that forms the bottom of the conduction band.…”
mentioning
confidence: 99%
See 1 more Smart Citation